In vitro assessment of plant growth-promoting potential of rhizosphere actinomycetes from Solanum tuberosum sp. andigena - Cisneros, Jessica (2020)
As part of the rhizosphere microbiota, actinomycetes interact with their host by releasing metabolites that positively influence their host’ growth. The main objective of this study was to evaluate the plant growth-promoting capacity of actinomycetes isolated from the rhizosphere of potato crops collected in the city of San Jeronimo, Andahuaylas, Peru. Forty-nine actinomycetes strains were isolated and screened for their capacity to solubilize phosphates, fix atmospheric nitrogen, produce indole acetic acid (IAA) and produce siderophores. Out of the total number of isolates, 33 (63.27%) solubilized phosphates, 42 (87.72%) fixed atmospheric nitrogen, 10 (20.41%) produced IAA and 18 (24.49%) were siderophore producers; strains AND 13 and AND 16 being the top performers. AND 13 was identified by 16S RNAr gene amplification as Streptomyces sp. The results indicate that actinomycetes can be considered as potential PGPR organisms and could be included in biofertilization programs of potato crops as an alternative to agrochemicals.